Pengaruh Motivasi Berwirausaha Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Di Kabupaten Majalengka - Asep qustolani; Nita Hernita (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The presence and role of entrepreneurs canhave an influence on economic improvement and the progress of a country. This research is motivated by the lowinterest in entrepreneurship among the people. This study aims to determine how the influence of Entrepreneurial Motivation and Entrepreneurship Knowledge on Interest in Entrepreneurship in the people of Majalengka Regency. The hypothesis proposed in this study is that Entrepreneurial Motivation and Entrepreneurship Knowledge have a significant effect on Entrepreneurial Interest partially. The population in this study is the people of Majalengka Regency who have knowledge about entrepreneurship, with a total sample of 100 people. The method used is a survey method with a descriptive verification approach. The analytical tool used in this research is multiple linear regression analysis, coefficient of determination, and hypothesis testing for partial test using t test. The results showed that partially entrepreneurial motivation and entrepreneurial knowledge had a significant effect on interest in entrepreneurship. This means that entrepreneurial motivation and entrepreneurial knowledge are the driving factors for increasing public interest in entrepreneurship.